Determinants of Economic Activity Choices: Case of Chinese Migrant in Congo Brazzaville - Kamitewoko, Edwige (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> If Chinese migrants carry out economic activities in the receiving country, one question arise which is of immediate economic interest: what determines the choice of these activities? Little research has been devoted to this issue. The paper uses a detailed Centre of Research and Prospective Studies survey data collected in 2013 in Brazzaville to analyze the factors that explain the choice of an economic activity for Chinese migrant using logit model. We found that four main determinants play a major role regarding this choice, namely: relational networks, province of origin, sex, primary level. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->